Acute environmental temperature variation affects brain protein expression, anxiety and explorative behaviour in adult zebrafish - S. Nonnis (Nature Portfolio, 2021)
Abstract This study investigated the effect of 4-d acute thermal treatments at 18 °C, 26 °C (control) and 34 °C on the nervous system of adult zebrafish (Danio rerio) using a multidisciplinary approach based on behavioural tests and brain proteomic analysis. The behavioural variations induced by thermal treatment were investigated using five different tests, the novel tank diving, light and dark preference, social preference, mirror biting, and Y-Maze tests, which are standard paradigms specifically tailored for zebrafish to assess their anxiety-like behaviour, boldness, social preference, aggressiveness, and explorative behaviour, respectively. Proteomic data revealed that several proteins involved in energy metabolism, messenger RNA translation, protein synthesis, folding and degradation, cytoskeleton organisation and synaptic vesiculation are regulated differently at extreme temperatures. The results showed that anxiety-like behaviours increase in zebrafish at 18 °C compared to those at 26 °C or 34 °C, whereas anxiety-related protein signalling pathways are downregulated. Moreover, treatments at both 18 °C and 34 °C affect the exploratory behaviour that appears not to be modulated by past experiences, suggesting the impairment of fish cognitive abilities. This study is the continuation of our previous work on the effect of 21-d chronic treatment at the same constant temperature level and will enable the comparison of acute and chronic treatment effects on the nervous system function in adult zebrafish.